PENGEMBANGAN PENGETAHUAN MASYARAKAT DESA PUNAGA KABUPATEN TAKALAR DALAM PENGELOLAAN LIMBAH ORGANIK DAPUR MELALUI KEGIATAN PELATIHAN PEMBUATAN ECO ENZYME - Ramadani, Muh. Fajar; Salsabila, Shopia; M, Ratna; Iskandar, Azizah Syahrani; Hajirah, Rizkyllah Nur; Azani, Syahrul Akbar; Putri, Nurul Edyawati; Junda, Muhammad (Universitas Negeri Makassar, 2024)
Punaga Village, Laikang District, Takalar Regency, is a village where the majority of residents are farmers and planters. Organic kitchen waste is a serious problem faced by many local communities, besides producing unpleasant odors, it can also disturb the beauty of the environment. This problem continues to exist due to the local community's lack of knowledge or skills in managing organic kitchen waste. So a service activity was carried out, namely training in making Eco enzyme. This training aims to increase public knowledge about the management of kitchen organic waste. Eco enzyme solution is the result of fermentation of leftover fruit and vegetables mixed with water and brown sugar. The method used in service consists of several stages including: (1) Observation and Interview, (2) Preparation Stage, (3) Implementation Stage. This activity is carried out by providing training and assistance directly to the community. This training was attended by 28 participants from several groups, including the village government, youth organizations, and the Punaga village community. In this training, participants were taught how to make Eco enzyme, starting from the ingredient preparation stage, making the mixture to the fermentation stage. The training participants were very enthusiastic about taking part in the training, the participants thought that this training was useful for them, because it could increase people's insight into managing waste. The result of this service is an increase in the community's potential in making Eco enzymes. Among the 28 participants who attended, there were 22 people who were categorized as being able to understand the material provided well. The next implication of this activity is that it can be used as a profit activity by selling products that have been made, so that this activity is sustainable.